The impact of economic factors upon housing prices in Malaysia market / Nurul Amira Zulkifli - Zulkifli, Nurul Amira (2007)
This project paper was designed to examine the impact of macroeconomic factors upon housing prices in Malaysia's market. It is difficult to predict how much housing prices would change due to the macroeconomic factors. This information is important to every income levels. The purpose of this study is to determine the relationship between macroeconomic factors and housing prices in Malaysia's market. This study also will provide the impact of macroeconomic factors on housing prices from 1996 to 2005 by using quarterly basis. In this study, the macroeconomic factors refer to interest rates, inflation rates and growth rate will be defined as independent variables. While the dependent variable is housing price index in Malaysia's market. This study will use Correlation Model and Multiple Regression Model as a statistical tool. To demonstrate the impact of macroeconomic factors upon housing prices in Malaysia's market, the data collected will be analyzed by the SPSS model. The finding shows there is a negative relationship between house price with inflation and interest rate. While the relationship between houses price in Malaysia is positive correlation.